Rodinný dům s podnikatelskou činností - Marášek, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Bakalářská práce se zabývá projektovou dokumentací rodinného domu s podnikatelskou činností. Novostavba se nachází v obci Prakšice v okrese Uherské Hradiště. Dům je osazen na mírně svažitém pozemku. Novostavba je členěna na dvě oddělené části. Obytná část tvoří dvě nadzemní podlaží a podnikatelská činnost zastoupená wellness provozem v podzemním podlaží. Zdivo i stropní konstrukce jsou navrženy ze systémových prvků Heluz. Střecha je sedlová se sklonem 35°.

The bachelor’s thesis deals with design documentation of a family house with business activity. The new building is located in a village Prakšice in Uherské Hradiště district. The house is situated on a gentle sloping land. The new building is divided into two separate units. It is a house with two floors and business activity represented by wellness establishment on the underground floor. The masonry and ceiling constructions are designed from Heluz system. The roof is saddle with a slope 35°.
Family house with a business activity
Keywords: Novostavba; rodinný dům; podnikatelská činnost; zdící systém Heluz; sedlová střecha.; A new building; family house; business aktivity; brick system called Heluz; saddle roof.